2009
DOI: 10.1016/j.bbamcr.2009.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional diversity in the family of small heat shock proteins from the parasite Toxoplasma gondii

Abstract: Small heat shock proteins (sHsps) are ubiquitous molecular chaperones which prevent the nonspecific aggregation of non-native proteins. Five potential sHsps exist in the parasite Toxoplasma gondii. They are located in different intracellular compartments including mitochondria and are differentially expressed during the parasite's life cycle. Here, we analyzed the structural and functional properties of all five proteins. Interestingly, this first in vitro characterization of sHsps from protists showed that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 65 publications
1
19
0
1
Order By: Relevance
“…Within protozoan, the Apicomplexa generated a main group, indicating a high similarity of the sequences of the different genera of Apicomplexa. A cluster for T. gondii consistent with previous reports was obtained, demonstrating that the proteins HSP20, HSP21, HSP29, and HSP30 are very similar to each other and that HSP28 (mitochondrial sHSP) is more distantly related, as was suggested by de Miguel et al (2009). N. caninum, an organism phylogenetically related to T. gondii, also appears to possess several members of sHSPs that, according to the tree topology in Fig.…”
Section: Sequence Analysis Of Shspssupporting
confidence: 87%
See 1 more Smart Citation
“…Within protozoan, the Apicomplexa generated a main group, indicating a high similarity of the sequences of the different genera of Apicomplexa. A cluster for T. gondii consistent with previous reports was obtained, demonstrating that the proteins HSP20, HSP21, HSP29, and HSP30 are very similar to each other and that HSP28 (mitochondrial sHSP) is more distantly related, as was suggested by de Miguel et al (2009). N. caninum, an organism phylogenetically related to T. gondii, also appears to possess several members of sHSPs that, according to the tree topology in Fig.…”
Section: Sequence Analysis Of Shspssupporting
confidence: 87%
“…It is unclear whether similar activities occur in vivo. However, sHSPs of certain parasites that were shown to have molecular chaperone activity in vitro were also overexpressed under conditions of cellular stress (de Miguel et al 2005;Wu et al 2007;de Miguel et al 2009;Pérez-Morales et al 2009) The accumulation of β-amyloid peptide (Aβ) in the human cerebral cortex is related to the pathogenesis of Alzheimer's disease; the ability of the Bbo20 protein of B. bovis to prevent the aggregation of this peptide was investigated. This inhibitory capacity has been reported for sHSPs of mammals; however, no studies have reported a concomitant decrease in the toxicity caused by Aβ peptides.…”
Section: Other Functions Of Shspsmentioning
confidence: 99%
“…19,23,26 In addition, however, quaternary structures composed of more or less subunits (12,32, and 50) seem to exist. 4,17,33,34 The subunits can be arranged in hollow spherical complexes. 4,14,16 Despite these variations, the common organizational subunit seems to be the dimer.…”
Section: Discussionmentioning
confidence: 99%
“…The most important structural feature of sHSPs is that they exclusively exist as multi-subunit oligomers, which had been observed 40 years ago on mammalian sHSPs (α-crystallin and Hsp27) (Spector et al 1971 ;Arrigo and Welch 1987 ;Longoni et al 1990 ) and later on many sHSPs from different organisms (Chang et al 1996 ;Haley et al 2000 ;Kim et al 1998 ;van Montfort et al 2001 ;de Miguel et al 2009 ;den Engelsman et al 2009 ;Haslbeck et al 1999Haslbeck et al , 2008Kennaway et al 2005 ;Shi et al 2011 ;Leroux et al, 1997b ;Giese and Vierling 2004 ;Sun et al 2004 ;Hilario et al 2011 ;Hockertz et al 1991 ;Merck et al 1993b ). Although subunits within a sHSP oligomer are theoretically identical in their substrate-binding residues, the architecture of such multi-subunits would enable the sHSP oligomer to incorporate substrate proteins at multiple independent sites.…”
Section: General Signifi Cance Of Oligomers For Substrate-bindingmentioning
confidence: 89%